Tinjauan Yuridis Terhadap Tindak Pidana Physical Sexual Harassment Yang Dialami Perempuan - Shelvi Rusdiana; Tantimin; Ling, Suryani (Jurnal Hukum Samudra Keadilan, 2023)
Sexual harassment against women is an act that does not reflect an attitude of caring between humans. Sexual harassment predominantly occurs in women due to the stigma that makes women as beings who have a weaker and lower position than men. The law functions to accommodate the community in order to provide security in public spaces. The function of law is to define societal norms, that law follows developments in societal behavior. This article uses normative legal research methods because this research originates from existing legal norms. With the type of legal approach, statutory regulations (Statue Approach), conceptual approach (Conceptual Approach) and case approach (Case Approach). The data used uses secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique used in writing this article was through literature study (Library Research) and analyzed using descriptive qualitative methods. So the general aim of the characteristics of this article is to find out what forms of legal protection exist for victims of physical sexual harassment crimes experienced by women in Indonesia.